1999
DOI: 10.1074/jbc.274.30.21369
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-dependent Localization of NAP-22 on a Neuronal Membrane Microdomain (Raft)

Abstract: A membrane microdomain called raft has been under extensive study since the assembly of various signaltransducing molecules into this region has been envisaged. This domain is isolated as a low buoyant membrane fraction after the extraction with a nonionic detergent such as Triton X-100. The characteristic low density of this fraction is ascribed to the enrichment of several lipids including cholesterol. To clear the molecular mechanism of raft formation, several extraction methods were applied to solubilize r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 63 publications
8
78
0
Order By: Relevance
“…It has been suggested that this cell membrane-Golgi pathway may regulate lipid raft distribution and function with recycling occurring continuously (51). Amyloid precursor protein and A␤ are associated with cholesterol-rich low density membrane domains (52)(53)(54)(55). Extracellular A␤ that is not highly aggregated may target lipid rafts, promoting cycling of lipid rafts to the Golgi complex.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this cell membrane-Golgi pathway may regulate lipid raft distribution and function with recycling occurring continuously (51). Amyloid precursor protein and A␤ are associated with cholesterol-rich low density membrane domains (52)(53)(54)(55). Extracellular A␤ that is not highly aggregated may target lipid rafts, promoting cycling of lipid rafts to the Golgi complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, this distribution was disrupted by cholesterol depletion with methyl‐β‐cyclodextrin (βMCD), a procedure known to disrupt lipid rafts (Maekawa et al . 1999). Similarly, co‐immunoprecipitation and PLA experiments revealed that the cholesterol depletion disrupted the interaction between ANO1 and IP 3 R1 in DRG neurons.…”
Section: Coupling Between Ano1 and Endoplasmic Reticulum; Is This A Gmentioning
confidence: 99%
“…Solubilization of PDE with MCD Extraction-It is known that the cholesterol-removing regent, methyl-␤-cyclodextrin, can solubilize a certain protein component of the Triton X-100-resistant membrane of rat brain (18). Thus, we examined the effect of MCD on the protein composition of DRM derived from light-and GTP␥S-exposed ROS.…”
Section: Rafts In Retinal Photoreceptors 20814mentioning
confidence: 99%